Functional analysis of each blue light receptor, cry1, cry2, phot1, and phot2, by using combinatorial multiple mutants in Arabidopsis - Ohgishi, Maki (National Academy of Sciences, 2004)
Blue light receptors in Arabidopsis include two types of proteins, cryptochromes and phototropins. Previous studies have suggested that the cryptochromes cry1 and cry2 function mainly in photomorphogenic responses and that the phototropins phot1 and phot2 mainly regulate photo-induced movements. Receptors in the same family have redundant functions, although their responses to the fluence rate of blue light differ. To uncover functions of blue light receptors that may be concealed by their functional redundancy, we conducted analyses of combinatorial multiple mutants of blue light receptors. Comparison of the responses of the quadruple mutant cry1 cry2 phot1 phot2 to blue light with those of related triple mutants revealed that cryptochromes function in blue light-dependent, random hypocotyl-bending and that phototropins function in one photomorphogenic response, cotyledon expansion. Microarray analysis suggested that cry1 and cry2 independently function as key regulators of early blue light-induced genes, whereas phot1 and phot2 play subsidiary roles in transcriptional regulation by blue light.